PSYCHOLOGICAL, SOCIAL, ECONOMIC DETERMINANTS OF BUYING BEHAVIOR: MODERATING INCOME, LITERACY ON PRICE, BRAND, REVIEWS (Contemporary Journal of Social Science Review, 2025)
The research explores psychological, social and economic factors of customer purchase decisions (CBD) in the consumer electronics B2C market in Pakistan. The results of the study are based on fourteen hypotheses that test the direct effects of price sensitivity (PS), brand image (BI), social influence (SI) and the convenience (CONV) on both digital literacy (DL) and CBD, as well as, the mediating role of digital literacy (DL) and moderating role of income level (IL) on the relationship between digital literacy (DL) and CBD. Empirical support is provided to all the paths that have been hypothesized. The digital literacy is a strong mediator (= 0.621, p